Treatment patterns and outcomes of Stage IIIB/IIIC melanoma in France, Germany and the UK: A retrospective and prospective observational study (MELABIS). Issue 5 (May 2017) - Harries, Mark; Mohr, Peter; Grange, Florent; Ehness, Rainer; Benjamin, Laure; Siakpere, Obukohwo; Barth, Janina; Stapelkamp, Ceilidh; Pfersch, Sylvie; McLeod, Lori; Wolowacz, Sorrel; A. Kaye, James; et al.
Summary: Aim: Real‐world data on treatment patterns/outcomes in patients with advanced melanoma, while scarce, are useful for health technology assessments that govern patient access in many countries. We collected retrospective data on treatment patterns among patients in France, Germany and the UK with Stage IIIB/IIIC melanoma with macroscopic lymph node involvement, whose primary melanoma and regional lymph node metastases had been completely resected. Methods: Patients ≥18 years were diagnosed between 1 January 2009 and 31 December 2011. Data were obtained from patients' medical records and a patient survey. Results: Forty‐nine centres provided data on 558 patients: 53.6% had Stage IIIB disease; 58.2% were of working age (<65 years), 22.5% reported a change in employment status due to melanoma, 8% were on long‐term sick leave; and 35.1% were deceased over the study period. Overall median distant metastases‐free survival was 23.4 months and median disease‐free survival was 13.3 months. Hospitalisation frequency increased during distant metastatic/terminal disease phases. Adjuvant therapy was received by 7.0% (14/199) of patients in France, 2.6% (5/195) in the UK, and 33.5% (55/164) in Germany. Low‐dose interferon was used more frequently than other regimens. High‐dose interferon was associated with discontinuation in 28.6% and dose delay/reduction in 33.3% of patients. Conclusions: Rapid disease progression combined with increased use of healthcare resources in later phases of disease result in a high burden‐of‐illness for patients and healthcare providers. The use of adjuvant interferon therapy varies considerably in this population in the countries studied, highlighting the need for improved treatments for melanoma.